The Role of the London Missionary Society and Church Missionary Society in the Abolition of "Oozhiyam" (Bonded Labor Service) in Kerala - Balakrishnan, Ayyappan (Journal for the study of religion, 2020)
Bonded labor is the most widespread form of slavery in the world. It is at once the most ancient and most contemporary face of human servitude. In India, "labor" is more a social category than economics, where the division of labor and laborer is defined according to the caste. The caste system is not a scientific division of labor, which is, after all, necessary for the efficient functioning of any economy. It is an arbitrary, birth-determined hierarchy in which different types of laborers are graded one above the other and subject to a descending scale of civil disabilities that have nothing to do with efficiency or productivity. It is not a division based on choice, as individual sentiment, preference, or even actual skill, have no place in it. Caste slavery was an oppressive, discriminative, and exploitive system which existed in Kerala from an early medieval period onwards. In the social structure of Kerala, the bonded or forced labor system was an unavoidable factor of slavery. As the system of bonded labor was associated with feudalism, land-based social relations were formed in the state. The oozhiyam or bonded labor system, therefore strictly connected with the caste oriented slavery in Kerala. Under the system of oozhiyam, the economically under-privileged servants were obliged to render bonded services on all days of the week as required by the government officials and the higher castes. The main force behind this system was the coercive authority of the government and the privileged class. Nobody dared to evade the services demanded by the government. Only on the days of the oozhiyam services, the laborers received a minimum quantity of food to keep their body and soul together. This essay mainly focuses on the ameliorating activities of the Christian missionaries, such as the London Missionary Society (LMS) and Church Missionary Society (CMS), among the oppressed sections of the society of Kerala. In addition to the social legislations of the government, the intervention of Christian missionaries also helped in the permanent abolition of the system of oozhiyam in Kerala.